AN OVERVIEW STATUS OF LITERACY AMONG RURAL ANDHRA PRADESH - Kosari, Dr.Ravindra (IJRDO - Journal of Applied Management Science, 2016)
In India, its organization and the progress that has been made Since independence. Different components that constitute Rural education infrastructure are evaluated for their relative Importance in the delivery of effective learning. We also examine the current status of rural education infrastructure in the country and gaps in the provisioning. the education policies of successive governments have built on the substantial legacies of the Nehruvian period, targeting the core themes of plurality and secularism, with a focus on excellence in higher education, and inclusiveness at all levels. In reaching these goals, the issue of funding has become problematic; governments have promised to increase state spending while realizing the economic potential of bringing in private-sector financial support. Paper also focus on Crude Literacy Rate in India by 2011, Literacy rate in Andhra Pradesh of India 2011 and Steps taken by government in accelerating Education planning in India.